Rekonstruksi Nilai-Nilai Sosial Qur’ani melalui Tafsir Tarbawi: Studi atas Surah Al-Hujurat Ayat 11–13 - Salamah, Salamah; Luthfi, Attabik; Muhayar, Marhadi; Adawiyah, Robiah; Anadri, Avisina (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This study aims to reconstruct Qur’anic social values through a tarbawi exegesis of the socio-educational principles contained in Surah Al-Hujurat, verses 11–13. Using a qualitative, literature-based research design, it examines classical and contemporary tafsir works, Islamic educational scholarship, and relevant social theories. The analysis explores how these verses offer moral and pedagogical foundations for cultivating a civilized social character. The findings demonstrate that the Qur’anic teachings—including prohibitions against mockery, safeguarding human dignity, avoiding suspicion, refraining from fault-finding and backbiting, and strengthening brotherhood—function as core principles of social education applicable to modern educational contexts. A tarbawi approach reveals that these values are not merely normative but have transformative potential in shaping learners to interact ethically, inclusively, and respectfully within diverse societies. Verse 13, emphasizing human equality and piety as the ultimate moral criterion, provides a framework for education that rejects discrimination and promotes social harmony. Thus, reconstructing Qur’anic social values through a tarbawi lens enriches the discourse on social education and contributes to fostering a more humanistic and dignified society.